Physical and superconducting properties of carbon nanofibers and carbon nanotubes YBa₂Cu₃O₇₋δ superconductor - Khalid, Nurul Auni (2016)
A co-precipitation (COP) process for the synthesis of ultrafine YBa2Cu3O7-δ (Y-123) precursor has been developed with the addition of carbon nanofibers (CNFs) and carbon nanotubes (CNTs) nanoparticles with varying amounts of weight percentage (wt. %). Both nanoparticles acted as pinning center to improve the transport critical current density (Jc). The objective of this study was to investigate the flux pinning capability from carbon sources of CNFs and CNTs in YBa2Cu3O7-δ superconductor. The effects of CNFs and CNTs addition on the superconducting properties (Tc and Jc), phase formation and structural properties, microstructure and surface morphology including the elemental distribution analysis were studied. A non-added Y-123 was used as a reference. The Jc for this sample is 11 A/cm2. Introduction of CNFs and CNTs improved Jc significantly. Furthermore, the volume fraction of Y-123 phase was 96.2 % and EDX showed excellent atomic ratio. CNFs addition significantly enhanced the Jc of Y-123 bulk. The x = 0.4 wt. % sample showed the optimal amount as it exhibited the highest Tc and Jc of 88.0 K and 830 A/cm2, respectively. CNTs addition showed Jc value of 477 A/cm2 for the x = 0.2 wt. % sample which gave the optimal amount of CNTs addition. The largest grain size and high percentage of Y-123 phase was also observed in this sample together with good atomic % from EDX and high Tc value. The enhancement of Jc using CNFs and CNTs as artificial pinning centers from this work indicated that these two compounds are suitable for flux trapping. Both samples show increased values of Tc and Jc towards the optimum wt. % of addition and decreased after further addition of dopants.